(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Deforestation occurs due to agriculture and agroforestry. Since it can alter the whole ecosystem and can change regional and global climate, Malaysia is one of the members of United Nation Framework on Climate Change (UNFCCC) which applies Kyoto protocol to curb this problem. Despite the large number of studies on rubber plantation, only a few studies focus on the development of allometric equation for estimating carbon sequestration for rubber plantation in Malaysia. This research studies the correlation of carbon sequestration and plant physiology of rubber trees using non-destructive sampling. In this research, the data were collected from rubber plantations in Selangor. The rubber trees chosen were in the range between 1 to 28 years old. The number of trees sampled in this research was 150 for each selected age (1, 2, 3, 5, 6, 8, 10, 13, 15, 17, 19, 20, 23 and 28 years) totalling 2100 trees. Allometric equation of this research was developed by using carbon sequestration as a response variable (Y) and 8 of the chosen predictor variables, which are diameter at breast height (DBH), height (HT), chlorophyll content (CC), stomatal conductance (SC), photosynthesis (PN), transpiration (TRPT), leaf area index (LAI) and age (AG). Based on the statistical indicators, the most suitable model is ln(Y) = c + aln(DBH) + bln(HT) + cln(AG). This model is highly reliable for its accuracy in measurement for forest managers to estimate carbon sequestration in rubber trees. Therefore, the research findings can be extrapolated accurately for managing secondary forests related to carbon balance. As for the additional explanatory variables such as CC, SC, PN, TRPT and LAI they do not fit the indicators’ goodness of fit for the equation. The research findings complement the previous research as well as the methodology of the Good Practice Guidance for Land Use and Land Use Change and Forestry (GPG-LULUCF).